2012
DOI: 10.1165/rcmb.2011-0182oc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Mouse Model of Empyema and the Mechanisms of Pleural Invasion by Streptococcus pneumoniae

Abstract: Although empyema affects more than 65,000 people each year in the United States and in the United Kingdom, there are limited data on the pathogenesis of pleural infection. We investigated the pathogenesis of empyema using animal and cell culture models of Streptococcus pneumoniae infection. The pathological processes during the development of empyema associated with murine pneumonia due to S. pneumoniae (strain D39) were investigated. Lungs were examined using histology, and pleural fluid and blood bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…We have demonstrated that for invasive strain 1861, invasion of the pleural cavity as early as 6 h postchallenge consistently precedes detection of bacteria in the bloodstream. This supports the notion that the pleural cavity may act as a conduit for bacteria to travel from the lung to the blood (8) and highlights this niche as an important site for investigation of hostpathogen interaction in pneumococcal disease.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We have demonstrated that for invasive strain 1861, invasion of the pleural cavity as early as 6 h postchallenge consistently precedes detection of bacteria in the bloodstream. This supports the notion that the pleural cavity may act as a conduit for bacteria to travel from the lung to the blood (8) and highlights this niche as an important site for investigation of hostpathogen interaction in pneumococcal disease.…”
Section: Discussionsupporting
confidence: 81%
“…1C). These data suggest that invasion of the blood leading to bacteremia is preceded by invasion of the pleural cavity, as has been previously proposed (8), and that invasion of the normally sterile pleural cavity may be used as an early marker of invasion. The data also show that whereas pleural cavity invasion by strain 1861 had commenced at 6 h, this was not due to a difference in bacterial numbers in the lung from those determined for strain 1 but was likely due to a difference in the interactions between the host and the two bacterial strains within the lung.…”
Section: Pleural Cavity Invasion As An Early Marker Of Invasive Capacsupporting
confidence: 80%
See 1 more Smart Citation
“…While murine EMP models (41) are attractive due to the availability of animals with different genetic backgrounds, they possess inherent limitations for studies of fibrinolysis (9). Murine PAI-1 (12), fibrin (33), and urokinase receptor, uPAR (22), structurally and functionally differ from those of the human proteins.…”
Section: Discussionmentioning
confidence: 99%
“…cigarette smoking could be a factor in the development of complicated pneumococcal infections, such as empyema (66). Through potential effects on alveolar epithelial permeability, alterations in pulmonary VEGF could also play a role in the development of the acute respiratory distress syndrome (ARDS) that may complicate pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%